A tumor necrosis factor α- and interleukin 6-inducible protein that interacts with the small subunit of DNA polymerase δ and proliferating cell nuclear antigen - He, Hua (The National Academy of Sciences, 2001)
A cDNA encoding a protein of 36 kDa, polymerase delta-interacting protein 1 (PDIP1), that interacts with the small subunit (p50) of DNA polymerase δ (pol δ) was identified in a two-hybrid screen of a HepG2 cDNA library by using p50 as bait. The interaction of PDIP1 with p50 was confirmed by pull-down assays, and a similar assay was used to demonstrate that PDIP1 interacts directly with the proliferating cell nuclear antigen (PCNA). PCNA and p50 bound to PDIP1 simultaneously, and PDIP1 stimulated pol δ activity in vitro in the presence, but not the absence, of PCNA, suggesting that PDIP1 also interacts functionally with both p50 and PCNA. Subcellular localization studies demonstrated that PDIP1 is a nuclear protein that colocalizes with PCNA at replication foci. A putative PCNA-binding motif was identified within the C terminus of PDIP1, and a synthetic peptide containing this PCNA-binding motif was shown to bind PCNA by far-Western analysis. Northern analysis demonstrated that PDIP1 mRNA is present in a wide variety of human tissues. PDIP1 was found to be highly homologous to a previously identified protein, B12 [Wolf, F. W., Marks, R. M., Sarma. V., Byers, M. G., Katz, R. W., Shows, T. B. & Dixit, V. M. (1992) J. Biol. Chem. 267, 1317–1326], one of the early response genes induced by tumor necrosis factor α. PDIP1 synthesis can also be induced by tumor necrosis factor α and by IL-6, cytokines essential for liver regeneration after loss of hepatic tissue. It is suggested that PDIP1 provides a link between cytokine activation and DNA replication in liver as well as in other tissues.